Answer:
2561.2785
Step-by-step explanation:
Answer:
10(x-3)
Step-by-step explanation:
Answer:
x = 0
Step-by-step explanation:
6 - 2x = 6x - 10x + 6
1. Isolate the variable (x)
6 - 2x = 6x - 10x + 6 -> 6 = 6x - 10x + 2x + 6
- Subtract 6 from both sides
6x - 10x + 2x + 6 -> 0 = 6x - 10x + 2x
2. Combine like terms
0 = 6x - 10x + 2x -> 0 = -2x
3. Solve
0 = x
*Note: 0 divided by anything is 0 so 0/-2 is 0
(unless it is 0/0 which equals 1)
Answer:
1.2 please tell me if im wrong
Step-by-step explanation: